Atlas of congenital cardiac disease - Abbott, Maude E. (Maude Elizabeth), 1869-1940 (desLibris. Books collection., 2006)
This reprint includes a short history of Abbott's life and how she came to create the Atlas, including a discussion of the material she used for her 1934 London Exhibit, which served as the basis for the Atlas. The original text and illustrations are enhanced by color prints of fifty-five specimens in the Abbott Collection of the McGill Pathology Museum.